随机因素影响下具有相关失效模式的齿轮传动动态可靠性研究 - 林希 (Jixie chuandong)
Considering the random fluctuation of the input torque and the load torque and the random meshing error,a lateral- torsional coupling dynamic model of single stage spur gear transmissions is built. By the numerical method,the dynamic stresses on the gear tooth are obtained. The process of dynamic stress during the work period is regard as a random process,and the probability distribution model of the maxima stress is equivalent to the effect of this random process in the random process,then,the probability distribution model of stress is obtained. After that,the probability distribution model of allowable stress is obtained by the Monte Carlo method. Based on the stress- strength interference theory,a dynamic reliability model of gear transmissions considering the correlation between the tooth root bending fatigue failure and the tooth surface contact fatigue failure is built. This research shows that the larger the meshing error is,the lower the reliability of system is.